Ventricular arrhythmia in heart failure patients with reduced ejection fraction and central sleep apnoea. Issue 3 (2nd August 2021) - Fisser, Christoph; Bureck, Jannis; Gall, Lara; Vaas, Victoria; Priefert, Jörg; Fredersdorf, Sabine; Zeman, Florian; Linz, Dominik; Wöhrle, Holger; Tamisier, Renaud; Teschler, Helmut; Cowie, Martin R.; et al.
Cheyne–Stokes respiration (CSR) may trigger ventricular arrhythmia in patients with heart failure with reduced ejection fraction (HFrEF) and central sleep apnoea (CSA). This study determined the prevalence and predictors of a high nocturnal ventricular arrhythmia burden in patients with HFrEF and CSA (with and without CSR) and to evaluate the temporal association between CSR and the ventricular arrhythmia burden.  This cross-sectional ancillary analysis included 239 participants from the SERVE-HF major sub-study who had HFrEF and CSA, and nocturnal ECG from polysomnography. CSR was stratified in ≥20% and <20% of total recording time (TRT). High burden of ventricular arrhythmia was defined as >30 premature ventricular complexes (PVCs) per hour of TRT. A sub-analysis was performed to evaluate the temporal association between CSR and ventricular arrhythmias in sleep stage N2.  High ventricular arrhythmia burden was observed in 44% of patients. In multivariate logistic regression analysis, male sex, lower systolic blood pressure, non-use of antiarrhythmic medication and CSR ≥20% were significantly associated with PVCs >30·h −1 (OR 5.49, 95% CI 1.51–19.91, p=0.010; OR 0.98, 95% CI 0.97–1.00, p=0.017; OR 5.02, 95% CI 1.51–19.91, p=0.001; and OR 2.22, 95% CI 1.22–4.05, p=0.009; respectively). PVCs occurred more frequently during sleep phases with versus without CSR (median (interquartile range): 64.6 (24.8–145.7) versus 34.6 (4.8–75.2)·h −1 N2 sleep; p=0.006).  Further mechanistic studies and arrhythmia analysis of major randomised trials evaluating the effect of treating CSR on ventricular arrhythmia burden and arrhythmia-related outcomes are warranted to understand how these data match with the results of the parent SERVE-HF study. High ventricular arrhythmia burden occurs in 44% of heart failure patients with reduced ejection fraction and central sleep apnoea. Arrhythmia burden is higher in sleep phases with versus without Cheyne–Stokes respiration. https://bit.ly/2QBDamC